Analisis Manajemen Risiko Pada Studi Kasus Penggelapan Dana di Bank Mandiri - Saddam, Muhammad; Nur Mubarok, Muadzin; Rasmana, Idan (Universitas Serambi Mekkah, 2024)
Bank Mandiri has a Bank Mandiri Risk Management Policy (KMRBM) which is used as the main guideline in implementing risk management. For more specific business fields, Bank Mandiri has more specific policies and procedures, for example in the areas of credit, treasury and operations. These policies and procedures, among other things, regulate the determination of limits for each activity, both at the portfolio and transactional levels. All policies and procedures at Bank Mandiri are a form of risk management inherent in every operational activity of Bank Mandiri which are evaluated and updated at least once a year. This research aims to identify what risks constitute cases of embezzlement at Bank Mandiri and to find out the most dominant risk factors at Bank Mandiri at the Rawa Lumbu Bekasi Sub-Branch Office. This research uses the Factor Analysis method. The conclusion of this research is that there are five identifications of risks at Bank Mandiri, Rawa Lumbu Bekasi Sub-Branch Office, consisting of loss classification, risk factors, sources of risk, types of risk, and ways of controlling risk.